2017
DOI: 10.1177/0022034517717261
|View full text |Cite
|
Sign up to set email alerts
|

Current and Emerging Treatments for Postsurgical Cleft Lip Scarring: Effectiveness and Mechanisms

Abstract: Cleft lip with or without cleft palate is the most common congenital malformation of the head and the third-most common birth defect. Surgical repair of the lip is the only treatment and is usually performed during the first year of life. Hypertrophic scar (HTS) formation is a frequent postoperative complication that impairs soft tissue form, function, or movement. Multiple lip revision operations are often required throughout childhood, attempting to optimize aesthetics and function. The mechanisms guiding HT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 65 publications
1
43
0
Order By: Relevance
“…Scarring in this situation can have an array of aesthetic and functional consequences for these young patients throughout their development. Hypertrophic scarring can be common following cleft lip repair – reported incidence rates of post-operative hypertrophic scarring vary but average around 25%, with rates varying by ethnicity and as high as 36.3% in Asian patients (Soltani et al, 2012; Papathanasiou et al, 2017). As previously discussed, hypertrophic scars can be itchy and painful and are associated with increased functional and cosmetic disability from scarring (Rabello et al, 2014).…”
Section: Clinical Correlate: Cleft Lip and Palatementioning
confidence: 99%
“…Scarring in this situation can have an array of aesthetic and functional consequences for these young patients throughout their development. Hypertrophic scarring can be common following cleft lip repair – reported incidence rates of post-operative hypertrophic scarring vary but average around 25%, with rates varying by ethnicity and as high as 36.3% in Asian patients (Soltani et al, 2012; Papathanasiou et al, 2017). As previously discussed, hypertrophic scars can be itchy and painful and are associated with increased functional and cosmetic disability from scarring (Rabello et al, 2014).…”
Section: Clinical Correlate: Cleft Lip and Palatementioning
confidence: 99%
“…Therefore, children with CLP are known to show greater oral tissue inflammation despite the same persistence of microorganisms than the children without cleft [4]. Relevant studies have indicated the inflammation of tissue as one of the main tissue modulators in the cleft affected regions due to the dysregulated chronic character of inflammation that disturbs the common tissue remodelation in normal wound healing [5]. However, there has been only very limited research done regarding the detection of main indicators of inflammatory process—pro- and anti-inflammatory cytokines into the cleft affected tissue.…”
Section: Introductionmentioning
confidence: 99%
“…The effect is a scar that is raised above the surface of the skin. The skin in the adjacent area, with the proper structure, elasticity and resilience are replaced by nonfunctional tissue mass 6,7 . Scar tissue leads to the creation of secondary deformities, such as deformed philtrum, Cupid's bow asymmetry, tight upper lip, whistle deformity, and irregularities in the functioning of orbicularis oris muscle 8,9 .…”
Section: Introductionmentioning
confidence: 99%